Plotting the Reading Experience : Theory/Practice/Politics - Oterholm, Knut, 1966-; Skjerdingstad, Kjell Ivar, 1964-; McKechnie, Lynne (Book collections on Project MUSE., 2016)
"It's a scholarly examination of the experience of reading--what it feels like, how it makes people feel, how people read and under what conditions--in various social, cultural, and political contexts. It contextualizes the reader's experience by putting it into dialogue with theories, practices, and politics."--